Civil liability for damages caused by the use of artificial intelligence: Applicable regime and security challenges for its development - Villarroel-Contreras, M (UNIV CHILE, FAC DERECHO, 2025)
Despite the increasing introduction of artificial intelligence into our daily lives, in Chile, unlike in comparative law, there is no sectoral regulation that creates a special civil liability regime or adapts an existing one to address damages resulting from its use. This article explores the alternatives that our legislation contemplates for dealing with damages derived from artificial intelligence, with the aim of explain the need to create a regulation in this sense. This is done through the analysis of the substantive and evidentiary difficulties generated by the traditional categories of civil liability of the Chilean general product liability regime to allow the imputation of civil liability for damages caused by intelligent systems.